2011
DOI: 10.1007/s11249-011-9865-8
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Friction and Wear Behaviour of an Electron Beam Melted Hypereutectic Al–Si Alloy

Abstract: The economic and environmental benefits of using light-weighting technology in automotive applications continue to attract attention for feasible commercial solutions. This study investigates the use of pulsed electron beam melting of a hypereutectic Al-Si alloy as a possible modification procedure for cylinder crankcase bore facing surfaces. Machined surfaces of an A390 alloy were subjected to five pulsed electron doses with an applied cathode potential between 16.5 and 36 kV. It was found that increasing bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…For example, Gao et al (2007) reported improved unlubricated wear behaviour of magnesium alloy after electron beam treatment due to improved surface hardness, as well as the formation of a homogenous passivating layer at the surface, resulting in improved corrosion behaviour. Walker et al (2011) also demonstrated improved wear behaviour of hypereutectic Al-Si alloy under dry conditions. Zou et al (2010) have also shown similarly improved properties in electron beam treated 316L steel, whereby after 20 shots a homogenous protective film was formed, improving its corrosion resistance, and increased surface hardness explained improved dry wear behaviour.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, Gao et al (2007) reported improved unlubricated wear behaviour of magnesium alloy after electron beam treatment due to improved surface hardness, as well as the formation of a homogenous passivating layer at the surface, resulting in improved corrosion behaviour. Walker et al (2011) also demonstrated improved wear behaviour of hypereutectic Al-Si alloy under dry conditions. Zou et al (2010) have also shown similarly improved properties in electron beam treated 316L steel, whereby after 20 shots a homogenous protective film was formed, improving its corrosion resistance, and increased surface hardness explained improved dry wear behaviour.…”
Section: Introductionmentioning
confidence: 81%
“…The phenomenon of crater formation associated with pulsed electron beam irradiation has been reported in a variety of alloys. For example by Gao et al (2007) in magnesium alloy, as well as in aluminium-silicon alloys by Walker et al (2011) and tool steel by Zou et al (2007). Craters are thought to form due to melting which starts just below the surface.…”
Section: Crater Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another modification of hypereutectic AlSi alloys is possible by electron beam melting of their surface. In [35] EBM is applied on A390 hypereutectic (16-18%Si) AlSi alloy. More about this process can be found in the mentioned literature.…”
Section: Other Manufacturing Processesmentioning
confidence: 99%
“…Over the past decade, LAEB has been applied to polish and improve the corrosion behaviour of mould surfaces [17][18][19], improve surface hardness in steels and magnesium alloys [20], as well as the wear resistance of Al-Si alloys [21,22]. More relevant to the current work, Guan et al [23] have observed localised amorphisation in a simple low-carbon steel by this process, giving evidence that the high-cooling rates associated with this technique can be applied for amorphous layer preparation.…”
mentioning
confidence: 99%